A Review : Developing Employability Basic Skills and Their Relevant Earning Techniques in the Animation Creative Industries - Khaled Alallan, Yousef; Ahmad Azaini, Manaf (Manuscript Central Publisher, 2020)
Various researchers been reviewed and studied to create a platform techniques solve this issues which is mandatory for employability job matching requirements, on the other hand . Various amounts of students could not achieve the acceptance for a job and impress employers in the interviews for multiple reasons mainly because individuals did not have the right skills such as communication skills, presentation, teamwork and problem solving. The techniques relay on the steps followed carefully for active solution in improving skill set.